2009
DOI: 10.1038/ijo.2009.166
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of overweight in preschool children: results of kindergarten-based interventions

Abstract: Objective: Given the increasing prevalence of pediatric obesity, we evaluated two kindergarten-based strategies for reducing overweight in preschool children in the Haute-Garonne Department in France. Methods: Kindergartens (n ¼ 79) were randomly assigned to one of the two strategies and followed for 2 years. In the first group (Epidémiologie et prévention de l'obésité infantile, EPIPOI-1), parents and teachers received basic information on overweight and health, and children underwent screening to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 29 publications
1
88
0
4
Order By: Relevance
“…studies seldom reported means and standard deviations), it was possible to conduct meta-analysis for only a small subset of interventions in this category (n = 13 targeted interventions). The fifty-two studies are therefore synthesised narratively in terms of whether they followed a universal (n = 16 44,45,57,64,[74][75][76][77]86,88,[96][97][98][100][101][102]104,105 ) or a targeted (n = 36 54,56,[58][59][60][61][62][63][65][66][67][68][69][70][71][72][73][78][79][80][81][82][83][84][85]87,[89][90][91][92][93][94][95]99,103,106 ) approach. The results are also summarised in Table 41 (universal-approach studies) and …”
Section: Targeted Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…studies seldom reported means and standard deviations), it was possible to conduct meta-analysis for only a small subset of interventions in this category (n = 13 targeted interventions). The fifty-two studies are therefore synthesised narratively in terms of whether they followed a universal (n = 16 44,45,57,64,[74][75][76][77]86,88,[96][97][98][100][101][102]104,105 ) or a targeted (n = 36 54,56,[58][59][60][61][62][63][65][66][67][68][69][70][71][72][73][78][79][80][81][82][83][84][85]87,[89][90][91][92][93][94][95]99,103,106 ) approach. The results are also summarised in Table 41 (universal-approach studies) and …”
Section: Targeted Interventionsmentioning
confidence: 99%
“…These interventions were targeted at populations of children regardless of their weight status, whereas the remaining 20 studies 44,45,59,60,84,87,88,[90][91][92][96][97][98][99][100][101][102][103][104][105][106] were treatment interventions for overweight and obese children. Sixteen 44,45,57,64,[74][75][76][77]86,88,[96][97][98][100][101][102]104,105 followed a universal approach and either included subgroup analysis of different SES groups or explored associations between SES and intervention outcomes. The remaining 36 studies 55,56,[58][59][60][61][62][63][65][66][67][68][69][70][71][72]…”
Section: Reducing Inequalities In Obesity Among Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Als Haupteinflussfaktoren wurden dabei Ernährungs-und Bewegungsinterventionen identifiziert, welche durch eine Verbesserung des Gesundheitswissens das Gesundheitsverhalten von Kindern und Jugendlichen nachhaltig positiv beeinflussen und somit das Risiko für die Entwicklung von Übergewicht und dessen Folgeerkrankungen reduzieren [7][8][9].…”
Section: Diskussionunclassified